Proposing Blockchain Technology Based Zakat Management Model to Enhance Muzakki’s Trust in Zakat Agencies: A Conceptual Study - Zulfikri Zulfikri; Salina Hj Kassim; Weni Hawariyuni (Universitas Syiah Kuala, 2021)
Objective – This study proposes a conceptual framework of Zakat based management model using blockchain technology with its transparent, secure, auditable, and efficient system in order to enhance the trust in zakat agencies. Design/methodology – This study is based on literature and theoretical reviews. This study took BAZNAS as the model of the Indonesian zakat agency to use Blockchain-based zakat payment on which zakat payers can track the fund allocated to the beneficiaries directly. Results – This research demonstrates the importance of Blockchain and smart contract technologies in zakat management by developing a model that combines zakat management agencies with the components of Blockchain and smart contract technologies. Research limitations/implications – The proposed model can contribute to the sustainability and efficiency of zakat agencies and is in line with the poverty eradication effort in Indonesia.